PENGELOLAAN RUANG TERBUKA HIJAU (RTH) HUTAN KOTA DI KOTA PEKANBARU - Melani "; Hasim As’ari As’ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Green open space (GOS) of urban forests is an important element in creating a aquality city in realizing the beautiful and sustainable development of Pekanbaru city and as a from of meeting the needs of green open space for the community. Management of urban forests GOS to the city of Pekanbaru is one way for the function and utilization of urban forests GOS to be felt by the community and also the animals that live in it. The management is carried out in the from of maintenance and repair and provision of facilities in urban green open space. The purpose of this study was to analyze how the management of green open space (GOS) of urban forests in the city of Pekanbaru as well as what factors influence the management of green open space (GOS) of urban forests in the city of Pekanbaru. The theory ised in this study is the theory of George R Terry who has 4 management principles, namely planning, organizing, implementing/driving, and controlling. The research method use is descriptive qualitative with file collection techniques through interviews, observation, and documentation. The selection of research informants used the purposive sampling technique. The results of this study indicate that there are factors that influence the management of green open space (GOS) of urban forests in the city of Pekanbaru. These factors are the budget provided, inadequate human resources. Inadequate supply of work material and equipment and user participation (User/visitors) in managing urban forests green open space in the city of Pekanbaru.Keywords: Green Open Space, Urban Forests, Managemen